Spatiotemporal Analysis Of Built-Up Area Dynamics In Karanganyar Regency (2015-2025) Using Ndbi And Google Earth Engine - Muhammad Nurul Huda; Rafi Sulthan Rizqullah; Azril Chairil; Denisa Aulia Pratiwi; Shalsabilla Aulia Putri; Nur Kahfi Mukhlisin Anwar; Listyo Yudha Irawan (Universitas Komputer Indonesia (UNIKOM), 2026)
Rapid urbanization in peri-urban regions has accelerated land use change, particularly through the expansion of built-up areas in locations adjacent to urban growth centers. Karanganyar Regency, which lies within the development influence of the Surakarta metropolitan region, has experienced increasing spatial pressure driven by residential expansion, economic activities, and improved regional accessibility. These conditions highlight the need for spatial monitoring of built-up area change to identify patterns of regional development over time. This study aims to identify changes in built-up areas in Karanganyar Regency during the 2015–2025 period. The analysis uses Landsat 8 OLI Surface Reflectance imagery processed through the Google Earth Engine platform, including stages of image selection based on study area boundaries and cloud cover, reflectance conversion, calculation of the Normalized Difference Built-up Index (NDBI), and classification of index values into four categories: non-building, sparse built-up, dense built-up area, and very dense building. The results show that the non-building class still dominates the regional area but decreased from 775.912 km² in 2015 to 739.897 km² in 2025. During the same period, all built-up classes increased in area, including sparse built-up from 20.436 km² to 44.816 km², dense built-up area from 5.989 km² to 16.514 km², and very dense building from 0.928 km² to 2.031 km². The spatial distribution of these changes indicates that built-up expansion tends to concentrate in western parts of the regency bordering Surakarta City and along major transportation corridors.